Probiotics and plant health - Kumar, Vivek (Associate Professor) (Springer, 2017)
This book primarily focuses on microbial colonization, its role in plant growth and nutrient cycling, mycorrhizae, and providing an overview of phytospheric microorganisms in sustainable crop systems. Despite the advances made in the study of plant-microbe synergism, the relation between microbes and plant health in the context of food security, soil nutrient management, human and plant health is still largely unexplored. Addressing that gap, the book presents reviews and original research articles that highlight the latest discoveries in plant probiotics, their specificity, diversity and function. Additional sections addressing nutrient management, human health, and plant microbiome management to improve plant productivity round out the coverage.
Keywords: Plants -- Microbiology.; Probiotics.; elektronické knihy; electronic books